Advertising Language Training for Digital Marketing Strengthening Mountainous Papua MSME Actors - Hasriani M; Syarifah; Ason Wakerkwa; Yuspin Lobo Sattu (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT MSME operators in the 3T regions of Papua Pegunungan face various challenges in digital marketing, including differences in linguistic backgrounds, which mean that crafting promotional messages in Indonesian is a skill that still needs to be further developed. This community service initiative aims to enhance the capabilities of MSME operators in Kuluakma Village, Walelagama District, Jayawijaya Regency, in utilizing advertising language as a digital marketing strategy. The method employed was participatory training combining lectures, live demonstrations, and group discussions, conducted in three sessions: an introduction to the functions of advertising language, an overview of social media platforms, and practical exercises in crafting promotional sentences. A total of 32 participants, comprising coffee farmers, beekeepers, and chicken farmers, took part in this activity. Evaluations based on pre-tests and post-tests showed an increase in participants’ ability to compose persuasive, informative promotional sentences that include a call to action in communicative Indonesian, rising from 6 to 17 participants. This activity is part of a multidisciplinary collaborative program that also includes training in digital marketing, product label design, and guidance on halal certification. Keywords: Advertising Language, 3T Regions, Digital Marketing, Participatory Training, Papua MSMEs